An evaluation of the antioxidant abilities of Allium species - Stajner, Dubravka; Szőllősi Istvánné Varga, Ilona (Acta Biologica Szegediensis, 2003)
In the present study we investigated antioxidative properties of leaves of different wild (Allium flavum L., Allium sphaerocephalum L., Allium atroviolaceum Bois., Allium vienale L., Allium scorodoprasum L.) and grown (Allium nutans L., Allium fistulosum L., Allium vienale L., Allium pskemense B. Fedtsch, Allium schenoprasum L., Allium cepa L., Allium sativum L.) Allium sorts were investigated. Activities of antioxidant enzymes (superoxide dismutase, catalase, peroxidase, glutathione peroxidase), quantities of malonyldialdehyde superoxide and hydroxyl radicals and reduced glutathione and also the content of total flavonoids, chlorophylls a and b, carotenoids, vitamin C and soluble proteins were determined. Our results indicate that leaves of grown Allium sativum L., Allium cepa L., Allium vineale L., Allium fistulosum L. and Allium nutans L. and wild Allium flavum L. and Allium ursinum L. exibited high antioxidant activites.